Diritti e democrazia in una dimensione costituzionale spirituale - Leonardo Bianchi (Democrazia e Diritti Sociali)
The essay develops relationship under constitutional profile between democratic principle and human rights and solidarity duties framework to the light of equality principle; also through the prism of constitutional principle of subsidiarity and fraternity, community personalism contributes to define a Constitution conception not only in a material, but in spiritual sense.